ANALISIS KEMAMPUAN KOMUNIKASI DAN MINAT BELAJAR MATEMATIS SISWA SMP - Abdul Muiz Muhtadi; Andika Nur Saputro; Anik Yuliani (Journal on Education, 2019)
This study aims to describe the abilities experienced by students as well as the factors that cause errors made by students in solving the problem of the number of quadratic equations and graphs of quadratic functions. This type of research is descriptive qualitative, with the subject of class IX C Middle School 1 Gunung Middle School Academic Year 2018/2019. Data collection techniques using the test method. The steps of analysis include data reduction, data presentation, and verification. Based on the results of data analysis it can be concluded that in solving quadratic equations and graphs the quadratic function makes a mistake; (1) ability to do questions, (2) ability to understand formulas, (3) ability to transform questions, (4) skill abilities. The causative factor is the communication skills of students who are low, inaccurate, are not accustomed to writing the elements that are known and asked on the questions, and the lack of students to put the results obtained into words.